Studi Meta-analisis: Empati dan Bullying - Tri Rejeki Andayani (Buletin Psikologi, 2012)
This article examines the corelation between empathy and bullying using meta-analytic techniques. The quantitave review includes 23 studies from 14 articles. Summary analysis providedsupport for the hypothesis that empathy has a negative correlation on bullying.